Catastrophic household expenditure for health care in low-income society: a study from Nouna District, Burkina Faso - Su, Tin Tin (Bulletin of the World Health Organization, 2006)
To quantify the extent of catastrophic household health care expenditure and determine the factors responsible for it in Nouna District, Burkina Faso. We used the Nouna Health District Household Survey to collect data on 800 households during 2000-01 for our analysis. The determinants of household catastrophic expenditure were identified by multivariate logistic regression method. Even at very low levels of health care utilization and modest amount of health expenditure, 6-15% of total households in Nouna District incurred catastrophic health expenditure. The key determinants of catastrophic health expenditure were economic status, household health care utilization especially for modern medical care, illness episodes in an adult household member and presence of a member with chronic illness. We conclude that the poorest members of the community incurred catastrophic health expenses. Setting only one threshold/cut-off value to determine catastrophic health expenses may result in inaccurate estimation leading to misinterpretation of important factors. Our findings have important policy implications and can be used to ensure better access to health services and a higher degree of financial protection for low-income groups against the economic impact of illness.